Are social media and mobile applications threatening retail websites? - Ramos, R.; Rita, P.; Moro, S. (International Journal of Internet Marketing and Advertising, 2023)
The use of mobile applications (MA) and social media (SM) platforms is reshaping the access to the internet. This study aims to analyse if consumers prefer to use a MA/SM platform or a retail website to search for a product or service and what are the reasons supporting their choice. Data was collected through unstructured interviews applied to internet consumers. A total of 770 replies were returned with their perspective analysed through text mining to uncover hidden patterns of knowledge. The outcome revealed that the vital aspect that makes consumers prefer a retail website is due to service quality. The choice for MA/SM platforms is its system quality in the act of searching for a product or service online. The demographic analysis exposed that younger generations prefer MA/SM, suggesting a different future for retail websites.